ELECTRONIC EDUCATIONAL MATERIALS IN TEACHING OF MATHEMATICS - GREGANOVA, Radomira; ORSZAGHOVA, Dana (Trends in education, 2008)
In the paper we are dealing with the new role of the usage of information and communication technologies at universities. IT become a part of the study of all taught university subjects. The study materials are created in the form of electronic study materials, on-line courses or web sites. At the Slovak University of Agriculture in Nitra the practical realization of this kind of educational ways and creation study materials is supported by LMS Moodle.
Keywords: teaching of mathematics; information technologies; web sites; electronic educational courses of mathematics